Directly elected mayors in urban governance - Sweeting, David (Policy Press, 2017)
This book is about the practices, roles and impacts of directly elected mayors in the cities that they govern. The volume draws on recent, original research evidence, to locate the debates on directly elected mayors in context in Europe, the US, and Australasia.